1987
DOI: 10.1007/bf00274794
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of diabetes mellitus in the rural region of Mali (West Africa): a practical approach

Abstract: A wide-range analytical study for screening diabetes mellitus in the rural region of the Republic of Mali was carried out on 7,472 subjects in whom fasting glycaemia was determined using reflectometry kits. Our results represent a breakthrough in the field of epidemiology of diabetes mellitus in West Africa. The prevalence rate of fasting hyperglycaemia equal to or over 7.00 mmol/1 was 0.92%. The statistical analysis of data collected in this manner showed an increased prevalence in the Caucasian and Fulani et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In 1976, T2D prevalence in Bamako was estimated at 1.4%, which was later estimated at 3.0% in 2017 16 , 20 . In a 1987 study at a referral center in Bamako, 0.9% of subjects with T2D resided in rural areas 12 , 14 , 21 . In 2017, a similar study approximately 90 miles from Bamako performed at a health center Sélingué health district reported T2D prevalence as 5.5% 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, T2D prevalence in Bamako was estimated at 1.4%, which was later estimated at 3.0% in 2017 16 , 20 . In a 1987 study at a referral center in Bamako, 0.9% of subjects with T2D resided in rural areas 12 , 14 , 21 . In 2017, a similar study approximately 90 miles from Bamako performed at a health center Sélingué health district reported T2D prevalence as 5.5% 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, the prevalence of diabetes was reported as 1.4% in Bamako, which was subsequently reported as 3.0% in 2017 among patients consulted through general medicine clinics 18,21 . In a study performed in 1987 at a referral center in Bamako, 0.9% of subjects with T2D resided in rural areas 14,16,22 . In 2017, a similar study reported T2D prevalence as 5.5% 18 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar trend can be found in studies carried out on diabetes in Mali. Here the issue has been mostly studied from an epidemiological (Fisch et al, 1987;Imperato et al, 1976) and a biomedical perspective (Beran & Yudkin, 2010;Besançon, 2009;Pichard et al, 1988;Sidibé et al, 2000). Anthropological research focuses on lay knowledge and practice of patients and health professionals (Gobatto & Tijou Traoré, 2011;Tijou Traoré, 2010, and attention is given to self-care and the way it has been supported by either public policies (Gobatto et al, 2016) or NGO programs (Besançon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%